The Conditional Reliability Evaluation of Data Center Network BCDC. (8th September 2020) - Lv, Mengjie; Cheng, Baolei; Fan, Jianxi; Wang, Xi; Zhou, Jingya; Yu, Jia
Abstract: As the number of servers in a data center network (DCN) increases, the probability of server failures is significantly increased. Traditional connectivity is an important metric to measure the reliability of DCN. However, the traditional connectivity of a DCN based on the condition of arbitrary faulty servers is generally lower. Therefore, it is important to increase the connectivity of a DCN by adding some limited conditions for the faulty server set. As a result, $g$ -restricted connectivity and $h$ -extra connectivity, which are two crucial subjects for a DCN's ability to tolerate faulty servers, were proposed in the literature. In this paper, we study the $g$ -restricted connectivity and $h$ -extra connectivity of a new server-centric DCN, called BCDC, based on crossed cube with excellent performance. We prove that the $g$ -restricted connectivity of BCDC is 4 for $n=3$ and $2n+g(n-2)-2$ for $n≥ 4$, where $0≤ g≤ n-3$, and the $h$ -extra connectivity of BCDC is 4 for $n=3$ and $2n+h(n-2)-2$ for $n≥ 4$, where $0≤ h≤ n-3$ .